1998
DOI: 10.1093/hmg/7.3.541
|View full text |Cite
|
Sign up to set email alerts
|

Spermine deficiency in Gy mice caused by deletion of the spermine synthase gene

Abstract: Two mouse mutations gyro (Gy) and hypophosphatemia (Hyp) are mouse models for X-linked hypophosphatemic rickets and have been shown to be deleted for the 5' and 3' end of the mouse homolog of PHEX (phosphate regulating gene with homologies to endopeptidases on the X chromosome; formerly called PEX), respectively. In addition to the metabolic disorder observed in Hyp mice, male Gy mice are sterile and show circling behavior and reduced viability. The human SMS (spermine synthase) gene maps approximately 39 kb u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
52
3

Year Published

1999
1999
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 30 publications
6
52
3
Order By: Relevance
“…Thus, even though Gy\Y cells have no spermine, the accumulation of spermidine was sufficient to affect their ODC activity adversely. This finding is at variance with that of Lorenz et al [26], who found that the ODC activity was elevated in all tissues analysed from Gy\Y mice. The difference is probably due to the fact that the spermidine concentration in the Gy\Y cells by far exceeded those in Gy\Y mouse tissues.…”
Section: Figure 5 Induction Of Ssat By Bespd In Gy/y Cells (>) and Incontrasting
confidence: 71%
See 4 more Smart Citations
“…Thus, even though Gy\Y cells have no spermine, the accumulation of spermidine was sufficient to affect their ODC activity adversely. This finding is at variance with that of Lorenz et al [26], who found that the ODC activity was elevated in all tissues analysed from Gy\Y mice. The difference is probably due to the fact that the spermidine concentration in the Gy\Y cells by far exceeded those in Gy\Y mouse tissues.…”
Section: Figure 5 Induction Of Ssat By Bespd In Gy/y Cells (>) and Incontrasting
confidence: 71%
“…When the phenotype of Gy mice was compared with that of Hyp mice, many additional defects became apparent. Although the Hyp and Gy mutations both affect the Phex gene, which encodes a neutral endopeptidase with significant homology to members of the membrane-bound metalloendopeptidase family, the Gy deletion extends far beyond the Phex gene and includes the upstream neighbour, the spermine synthase gene [25][26][27]. In fact, the deletion encompasses the entire spermine synthase gene and approx.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations